IMPACTS OF CLIMATE VARIABILITY ON SUSTAINABLE AGRICULTURAL WATER MANAGEMENT IN YAURI, NORTHWESTERN, NIGERIA - Ahmad, Lawal; Adigun, Habeeb Adekunle; Aliyu, Muzzamil; Wakawa, Daniel Thlama; Damana, Usman Muhammad (FUDMA Journal of Sciences, 2025)
Climate variability is greatly affecting water management and agricultural productivity particularly in semi-arid region like Yauri which experiences both flood and drought. This study examines the impacts of climate variability on sustainable agricultural water management in Yauri, Northwestern, Nigeria, using 30 years of meteorological data integrated with field surveys of agricultural water management practices. Descriptive statistics, including the Precipitation Concentration Index (PCI), Temperature Anomaly Index (TAI), Mann-Kendal trend test, and Sen’s Slope Estimator were applied to assess rainfall and temperature variability, trends, and anomalies. Total seasonal rainfall, onset, cessation, and length of growing season were also analyzed to determine implications for agricultural water use. Results show an average annual rainfall of 110.3 mm with 20.49 % coefficient of variation, indicating moderate variability. The rainy season lasted 135-178 days (average 164 days). PCI values (16.30-23.81) indicated moderate to irregular rainfall distribution, while trend analysis revealed a slight but statistically insignificant rise in seasonal rainfall ( . Temperature trends show a significant increase in minimum temperature (+0.074 , p<0.001), and a modest rise in maximum temperature (+0.0346 , signifying a warming trend. The TAI indicated pronounced dry-season warming and wet-season cooling anomalies Field Surveys revealed 84.66 % of farmers depend on groundwater, 91.35 % use traditional surface irrigation, and over 80 % lack water storage facilities. Key challenges include poor policy awareness, inadequate infrastructure, and inefficient water use. The study demonstrates that rising temperatures and erratic rainfall are affecting water availability and agriculture in Yauri, and recommends the implementation of smart-climate technologies,...